A Study on Cyber Security Using Blockchain Technology (International Journal of Food and Nutritional Sciences, 2022)
Blockchain is posing a threat to the established Internet's centralized trust infrastructure by advocating for a new approach to network architecture based on decentralization, transparency, and audibility. In a perfect world, blockchain would create an Internet that is decentralized, transparent, and more democratic. Blockchain, which is a trustworthy and decentralized database, has applications in a diverse range of industries, including the energy industry, agriculture, fishing, mining, recycling and reuse, air quality tracking, management of supply chains, and also the activities related to these. Several cybersecurity-related applications of Blockchain were examined in this paper. The author analyzed the three vulnerable areas of IT and the methods by which Blockchain has been shown to provide security. Furthermore, this study discussed that in the future, scholars should concentrate on a single Blockchain from which to construct cybersecurity apps to facilitate integration and consistency across solutions.